Avoiding Election Crimes: Learning from Conflicts in the Election of Regional Heads and Deputy Regional Heads (Law Research Review Quarterly, 2018)
One manifestation of a democratic state is the holding of general elections. Elections in Indonesia are used to elect the President and vice president, members of the DPR, DPD and DPRD, and Regional Heads. Since 2005, the people have been given the opportunity to elect their regional head leader directly. On one side this shows the state is trying to provide maximum opportunities for democracy to the people, but on the other hand the implementation of post-conflict local elections is not without obstacles, in addition to very expensive costs also its implementation is still prone to conflict, political manipulation, fraud, injustice, mobilization, money political, etc., up to many disputes over the results of the post-conflict local elections which lead to the Constitutional Court, even to the point of committing criminal offenses. The background of post-conflict local election conflicts is the existence of pairs of candidates for regent and deputy regent who do not accept the decisions issued by KPU, due to systematic, structured and massive violations committed by election participants, and KPU is not transparent in recapitulation of vote counting, unfair, dishonest, undemocratic, fraudulent, and unconstitutional.